Pembelajaran di Era Teknologi Digital – Sebuah Kajian Literatur - Siregar, Roswani; Subagiharti, Heni; Handayani, Diah Syafitri; Surbakti, Syamsul Bahri; Barus, Efendi (Journal of Education, Humaniora and Social Sciences (JEHSS), 2024)
The use of technological devices has brought changes in learning methods and strategies in the last decade. This article aims to describe a general overview of what educators have done in dealing with learning in the digital era in the last five years. The method used in this study is a literature review, namely by examining the results of 38 reports about learning using digital technology published in journals and proceedings between 2018 and 2023. Based on the results, several important aspects regarding learning in the digital era were found, namely from the perspective of various learning activity results in the last five years. The findings of this study show that digital-based teaching is not just about optimizing technology or the internet in developing students' thinking potential but is also related to developing students' attitudes, behavior, and personality. Apart from that, collaboration between educators and students is also important to maximize the impact of technology on learning. With the right approach, technology can become a powerful tool in achieving educational goals and allows its use to be tailored to students' needs.